LINGUOCULTURAL CHARACTERISTICS OF ANTHROPONYMS IN THE EPIC “LISON UT-TAYR” - Sayfullayeva, Fatima Bakhodir qizi (Educational Research in Universal Sciences, 2023)
In this article, the linguistic and cultural characteristics of the anthroponyms in Navoi’s epic "Lison ut-Tair" were studied. Types of anthroponyms such as names, nicknames, nicknames were discussed. Linguistic and cultural characteristics of anthroponyms were revealed through verses.